IKZF1 expression is a prognostic marker in newly diagnosed standard-risk multiple myeloma treated with lenalidomide and intensive chemotherapy: A study of the German Myeloma Study Group (DSMM) - Kroenke, J.; Kuchenbauer, Florian; Kull, M.; Teleanu, V.; Bullinger, Lars; Bunjes, D.; Greiner, A.; Kolmus, S.; Koepff, S.; Schreder, M.; Muegge, L-O; Straka, C.; et al. (Leukemia, 2017)
Lenalidomide is an immunomodulatory compound with high clinical activity in multiple myeloma. Lenalidomide binding to the Cereblon (CRBN) E3 ubiquitin ligase results in targeted ubiquitination and degradation of the lymphoid transcription factors Ikaros (IKZF1) and Aiolos (IKZF3) leading to growth inhibition of multiple myeloma cells. Recently, Basigin (BSG) was identified as another protein regulated by CRBN that is involved in the activity of lenalidomide. Here, we analyzed the prognostic value of IKZF1, IKZF3, CRBN and BSG mRNA expression levels in pretreatment plasma cells from 60 patients with newly diagnosed multiple myeloma uniformly treated with lenalidomide in combination with intensive chemotherapy within a clinical trial. We found that IKZF1 mRNA expression levels are significantly associated with progression-free survival (PFS). Patients in the lowest quartile (Q1) of IKZF1 expression had a superior PFS compared with patients in the remaining quartiles (Q2-Q4; 3-year PFS of 86 vs 51%, P=0.01). This translated into a significant better overall survival (100 vs 74%, P=0.03). Subgroup analysis revealed a significant impact of IKZF1, IKZF3 and BSG expression levels on PFS in cytogenetically defined standard-risk but not high-risk patients. Our data suggest a prognostic role of IKZF1, IKZF3 and BSG expression levels in lenalidomide-treated multiple myeloma.
CRIS-Team Scopus Importer:2023-03-23